The Influence of Sharia Financial Literacy, Technological Advances, Return Expectations, and Minimum Capital on Generation Z's Interest in Investing in the Sharia Capital Market - Muhimmatul Rizza; Edi Susilo (Department of Islamic Banking, 2024)
This study investigates the influence of Sharia financial literacy, technological advancement, return expectations, and minimum capital on the investment interest of Generation Z in the Sharia capital market of Jepara Regency. Using a quantitative method, the research targets Generation Z individuals in Jepara Regency, irrespective of their investment status. Data were collected through Google Forms questionnaires distributed to 100 participants. Analysis, conducted using SPSS version 25, revealed that 71.8% of Generation Z's investment interest in the Sharia capital market is influenced by the studied factors, while 28.2% is affected by other factors not included in the model. This study significantly contributes to understanding what drives Generation Z's interest in Sharia investments, offering valuable insights for the Sharia finance sector. The findings highlight the importance of enhancing financial literacy, technological adoption, and accessibility to attract more Generation Z investors to the Sharia capital market.